A survey of East Palaearctic Gnaphosidae (Araneae). 11. New data on Gnaphosidae (Araneae) from Tajikistan - Fomichev, Alexander A.; Marusik, Yuri M. (Zootaxa, 2021)
Three new species namely Drassodex tajikistanicus sp. n. (♂), Zelotes anatolyi sp. n. (♂) and Zelotes khatlonicus sp. n. (♂♀) are described from Khatlon Region of Tajikistan. A new combination is proposed as Poecilochroa hamipalpis (Kroneberg, 1875) comb. n. (ex. Echemus), accompanied with a redescription of the species. Nomisia palaestina (O. Pickard-Cambridge, 1872), a species previously known from Greece to Iran is recorded in Tajikistan (and Central Asia) for the first time, which is the northeasternmost record of this species globally. Descriptions, figures, diagnoses and local distribution maps of the treated species are provided.